Transitional palliative care interventions for older adults with advanced non-malignant diseases and frailty: a systematic review. Issue 4 (17th June 2020) - Sezgin, Duygu; Hendry, Anne; Liew, Aaron; O'Donovan, Mark; Salem, Mohamed; Carriazo, Ana María; López-Samaniego, Luz; Rodríguez-Acuña, Rafael; Kennelly, Siobhan; Illario, Maddalena; Arnal Carda, Cristina; Inzitari, Marco; et al.
Abstract : Purpose: To identify transitional palliative care (TPC) interventions for older adults with non-malignant chronic diseases and complex conditions. Design/methodology/approach: A systematic review of the literature was conducted. CINAHL, Cochrane Library, Embase and Pubmed databases were searched for studies reporting TPC interventions for older adults, published between 2002 and 2019. The Crowe Critical Appraisal Tool was used for quality appraisal. Findings: A total of six studies were included. Outcomes related to TPC interventions were grouped into three categories: healthcare system-related outcomes (rehospitalisation, length of stay [LOS] and emergency department [ED] visits), patient-related outcomes and family/carer important outcomes. Overall, TPC interventions were associated with lower readmission rates and LOS, improved quality of life and better decision-making concerning hospice care among families. Outcomes for ED visits were unclear. Research limitations/implications: Positive outcomes related to healthcare services (including readmissions and LOS), patients (quality of life) and families (decision-making) were reported. However, the number of studies supporting the evidence were limited. Originality/value: Studies examining the effectiveness of existing care models to support transitions for those in need of palliative care are limited. This systematic literature review identified and appraised interventions aimed at improving transitions to palliative care in older adults with advanced non-malignant diseases or frailty.